Urfolksrätt i den gröna omställningen - En rättslig analys av samernas rätt till FPIC vid etableringen av vindkraft i Sápmi ur ett miljörättviseperspektiv - Rosenmüller,Mathilda (2025)
The expansion of wind power as part of Sweden’s green transition has led to increased development in Sápmi, with consequences for Sámi culture. Sámi representatives have linked this exploitation to the historical dispossession of Sámi land and referred to it as green colonialism. At the same time, the Sámi people are particularly affected by the climate change that wind power is intended to mitigate. Therefore, this thesis aims to examine how the Sámi people’s rights as an Indigenous people, particularly the right to free, prior and informed consent (FPIC), are respected under Swedish law in the context of the green transition, with focus on wind power development in Sápmi. FPIC requires that states consult and cooperate with Indigenous peoples in order to obtain their consent prior to implementing measures or projects that may affect them. The principle is composed of three cumulative rights: the right to participation, the right to consultation, and the right to lands, territories, and resources. Given that the Sámi are affected both by the consequences of exploitation and by climate change, this raises the question whether such development can be considered just, from the perspective of environmental justice. Against this background, the thesis analyses wind power expansion and the Sámi people’s right to FPIC through the lens of different environmental justice concepts and examines the extent to which these concepts are fulfilled in this context. Based on legal analytical method, the thesis investigates the requirements of FPIC, as expressed particularly in UNDRIP and ILO No. 169, with reference to interpretations by international bodies, and how this right is fulfilled within Swedish law. The thesis concludes that the Sámi people’s right to FPIC cannot be fulfilled when the Swedish state focuses solely on the procedural aspect of consulta-tion, without considering human rights and the broader context in which con-sultation exists. Collective rights are not recognised as human rights, while individual rights are prioritised, which risks reinforcing historical powerstructures and contributing to green colonialism. For FPIC to be implemented in a meaningful way, the Sámi people’s right so self-determination must be respected, their collective rights must be recognised as human rights, and these rights must be given real weight in decision-making processes. If this does not occur, the different concepts of environmental justice cannot be fully realised.
Keywords: Folkrätt; Urfolksrätt; Samerätt; FPIC; Vindkraft